Maize w3 disrupts homogentisate solanesyl transferase (ZmHst) and reveals a plastoquinone‐9 independent path for phytoene desaturation and tocopherol accumulation in kernels. (15th February 2018) - Hunter, Charles T.; Saunders, Jonathan W.; Magallanes‐Lundback, Maria; Christensen, Shawn A.; Willett, Denis; Stinard, Philip S.; Li, Qin‐Bao; Lee, Kwanghee; DellaPenna, Dean; Koch, Karen E.
Summary: Maize white seedling 3 ( w3 ) has been used to study carotenoid deficiency for almost 100 years, although the molecular basis of the mutation has remained unknown. Here we show that the w3 phenotype is caused by disruption of the maize gene for homogentisate solanesyl transferase (HST), which catalyzes the first and committed step in plastoquinone‐9 (PQ‐9) biosynthesis in the plastid. The resulting PQ‐9 deficiency prohibits photosynthetic electron transfer and eliminates PQ‐9 as an oxidant in the enzymatic desaturation of phytoene during carotenoid synthesis. As a result, light‐grown w3 seedlings are albino, deficient in colored carotenoids and accumulate high levels of phytoene. However, despite the absence of PQ‐9 for phytoene desaturation, dark‐grown w3 seedlings can produce abscisic acid (ABA) and homozygous w3 kernels accumulate sufficient carotenoids to generate ABA needed for seed maturation. The presence of ABA and low levels of carotenoids in w3 nulls indicates that phytoene desaturase is able to use an alternate oxidant cofactor, albeit less efficiently than PQ‐9. The observation that tocopherols and tocotrienols are modestly affected in w3 embryos and unaffected in w3 endosperm indicates that, unlike leaves, grain tissues deficient in PQ‐9 are not subject to severe photo‐oxidative stress. In addition to identifying the molecular basis for the maize w3 mutant, we: (1) show that low levels of phytoene desaturation can occur in w3 seedlings in the absence of PQ‐9; and (2) demonstrate that PQ‐9 and carotenoids are not required for vitamin E accumulation. Significance Statement: We show that the classic maize mutant white seedling 3 ( w3 ) is caused by plastoquinone‐9 (PQ‐9) deficiency resulting from disruption of the maize gene for homogentisate solanesyl transferase, thus explaining the metabolic underpinnings of the w3 phenotype. Surprisingly, we found that w3 mutants retained low levels of phytoene desaturease (PDS) activity even in the absence of PQ‐9, counter to our previous understanding of PQ‐9 as a requisite cofactor for PDS.